Mengukur Tingkat Kepuasan Pelanggan Terhadap Pelayanan Di Toko Lunas Menggunakan Metode Fuzzy Associative Memory - Winda Ayu Astuti; Murni Marbun (Pustaka Timur Publisher, 2021)
The rapid advancement of information technology can help in measuring the level of customer satisfaction. The level of customer satisfaction is one of the important things to note because customer satisfaction is very influential on the success of a business being run. This study aims to build an application to measure customer satisfaction with the services provided by sellers at Toko Lunas. Measuring the level of customer satisfaction using the Fuzzy Associative Memory (FAM) method. FAM is a model used using an artificial neural network, where the network structure is interpreted with a set of fuzzy rules. FAM has the advantage that it can improve the ability of intelligent systems to learn and adapt to environments with variations in data that are incomplete and precise. The test is carried out based on 5 assessment criteria in measuring customer satisfaction with services, namely assessment, responsiveness, empathy, direct evidence, and assurance that can help measure customer satisfaction. The application is built based on desktop programming which can be used by entering the value provided by the customer. The results showed that the implementation of the system can provide information about the level of customer satisfaction with the services provided by the seller at Toko Lunas.